Выражение: а) (х-3)^2 + х(х+9) б) (2а+5)^2-5(4а+5) в) 9b (b-+2)^2 г) (b-4)^2+(b-1)(2-b) д)(a+3)(5--1)^2 е) (5+2у)(у--2у)^2

lana770 lana770    3   31.07.2019 17:20    0

Ответы
SherlockAlya SherlockAlya  03.10.2020 18:52
=х²-6х+9+х²+9х=2х²+3х+9
=4а²+20а+25-20а-25=4а²
=9в²-9в-9в²-12в-4=-21в-4
=5а-а²+15-3а-а²+2а-1=-2а²+4а+14
=5у-15+3у²-6у-25+20у-4у²=-у²+19у-40
ПОКАЗАТЬ ОТВЕТЫ
kakniet kakniet  03.10.2020 18:52
(x-3)^2+x(x+9)=x^2-6x+9+x^2+9x=2x^2+3x+9
(2a+5)^2-5(4a+5)=4a^2+20a+25-20a-25=4a^2
9b(b-1)-(3b+2)^2=9b^2-9b-9b^2-12b-4=-21b-4
(b-4)^2+(b-1)(2-b)=b^2-8b+16+2b-b^2-2+b=-5b+14
(a+3)(5-a)-(a-1)^2=5a-a^2+15-3a-a^2+2a-1=-2a^2+4a+14
(5+2y)(y-3)-(5-2y)^2=5y-15+2y^2-6y-25+20y-4y^2=-2y^2+19y-40
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика